Subaru Hyper Suprime-Cam view of quasar host galaxies at z < 1 - Ishino, Toru; Matsuoka, Yoshiki; Koyama, Shuhei; Saeda, Yuya; Strauss, Michael A; Goulding, Andy D; Imanishi, Masatoshi; Kawaguchi, Toshihiro; Minezaki, Takeo; Nagao, Tohru; Noboriguchi, Akatoki; Schramm, Malte; et al. (Publications of the Astronomical Society of Japan, 2020)
Abstract Active galactic nuclei (AGNs) are key in understanding the coevolution of galaxies and supermassive black holes (SMBHs). AGN activity is thought to affect the properties of their host galaxies via a process called “AGN feedback,” which drives the coevolution. From a parent sample of 1151 z < 1 type-1 quasars from the Sloan Digital Sky Survey quasar catalog, we detected the host galaxies of 862 of them in the high-quality grizy images of the Subaru Hyper Suprime-Cam survey. The unprecedented combination of the survey area and depth allowed us to perform a statistical analysis of the quasar host galaxies, with small sample variance. We fitted the radial image profile of each quasar as a linear combination of the point spread function and the Sérsic function, decomposing the images into the quasar nucleus and the host galaxy components. We found that the host galaxies are massive, with stellar mass Mstar ≳ 1010 $M_\odot$, and are mainly located on the green valley. This trend is consistent with a scenario in which star formation in the host galaxies is suppressed by AGN feedback, that is, AGN activity may be responsible for the transition of these galaxies from the blue cloud to the red sequence. We also investigated the SMBH mass to stellar mass relation of the z < 1 quasars, and found a consistent slope with the local relation, while the SMBHs may be slightly undermassive. However, the above results are subject to our sample selection, which biases against host galaxies with low masses and/or large quasar-to-host flux ratios.